Ghada Mahat: whistling against the odds—female refereeing, gender dynamics, and resistance in Algerian soccer - Mahfoud Amara (7236599) (2025)
This study examines Ghada Mahat’s historic role as Algeria’s first female referee in a high‑profile men’s soccer match, exploring its impact on gender, power, and resistance in Algerian soccer. Mahat’s appointment challenges patriarchal norms but also provokes resistance, reflecting broader socio-political tensions in Algerian society. Using media content analysis and social media discourse, the study investigates how Mahat’s role is framed in media narratives and public debate. While celebrated as a trailblazer, Mahat faces media bias, gendered scrutiny, and cultural opposition, exposing the paradox of symbolic inclusion, where visibility does not guarantee meaningful gender equity. This study highlights the ongoing need for policy reforms, improved institutional support, and proactive measures to address the structural inequalities that marginalize female referees in Algerian soccer. Other Information Published in: Sport in Society License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/17430437.2025.2590520